Study the Physicochemical Characteristics of the Treatment Wastewater of AL-Rasheed Factory for Vegetable Oils â€“Baghdad - Aghalee, N. N.; Basat, S. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research presents the results of the tests of the physical, chemical and biological treatments performed on the industrial effluent of Al-Rashid Factory for vegetable oils during January to July, 2010. Some environmental parameters such as temperature, electrical conductivity(ec), Biological oxygen demand(bod), chemical oxygen demand(cod), total suspended solids(tss), dissolved oxygen(o2) and total dissolved solids(tdc) have been investigated. The study shows that the industrial effluent contains a percent of organic pollution and in different values, and that it is responsible for the (bod), which records (5.15-67)ppm, while the (cod) ranges between (25-170.5)ppm, the (ec) values range between (1360-3330)mm hose per cm, the (tds) values were between (6.65-72 )ppm, while (tss) values ranged from (812-2000)ppm, (do) values recorded were from (2.2-9.25)ppm, and the highest temperature value recorded was in July which is 40 Â°C.